A study into cyber risks with respect to SMART port development - Thong, Jovy Yunxi (Nanyang Technological University, 2023)
Ports around the world are constantly developing and integrating the latest technologies to stay competitive and become more efficient. As more ports are upgrading, smart ports have opportunities to leverage technologies as well as introduce risks that come with using such technologies. Cyber risks are a constant threat to ports and can cause detrimental economic losses and influence the supply chain. As such, there are international frameworks and national policies implemented to deal with such risks. This paper aims to investigate the effectiveness of frameworks, regulations, and policies that are in place. Research was conducted to identify weaknesses of such policies and suggest possible solutions to strengthen the implementation and support of regulations.